Enhancing urban governance efficiency through the egovernment of Malaysian local authorities – the case of Subang Jaya - Azmizam Abdul Rashid; Hamzah Jusoh; Jalaluddin Abdul Malek (Faculty of Social Sciences and Humanities, UKM,Bangi, 2010)
The electronic government (e-government) initiative in Malaysia was launched to lead the country into the Information Age. The vision was for government and businesses people to work together for the benefit of the nation through improved convenience, accessibility and quality of interactions resulting from better information flows, processes, speed and quality of policy development, coordination and enforcement. This paper describes how this vision of e-government had been achieved by the Majlis Perbandaran Subang Jaya (MPSJ) local authority. Seven factors were behind this success of the MPSJ’s implementation of the e-government, namely, the willingness of the local authority to commit to e-government and depart from existing ways of doing things; the willingness of the local authority’s top management to lead the way to e-government; seamless e-government services that encouraged different agencies to work closely with the MPSJ; the ICT skills building capability and capacity of the MPSJ officers; the development of an egovernment public-private partnership framework; the ability of the MPSJ management to overcome costrelated problems in the implementation of e-government; and, the ability of the MPSJ management to monitor and evaluate the impact and benefits of the e-government programme in order to justify continued political and public support. The achievement notwithstanding, the paper identifies further rooms for improvement, namely, the introduction of e-submission to enable the electronic transfer and management of Computer-Aided Drawings (CAD) and related documents through the creation of a Wide Area Network(WAN); and, the application of GIS (GIS-MPSJ) for the computer processing of geographically referenced data.